Association of Short-Term Mortality of Venous Thromboembolism with Family History of Venous Thromboembolism and Charlson Comorbidity Index - Zöller, Bengt; Pirouzifard, MirNabi; Sundquist, Jan; Sundquist, Kristina (Thrombosis and Haemostasis, 2019)
Studies on short-term prognosis of venous thromboembolism (VTE) that take family history of VTE and Charlson Comorbidity Index (CCI) into account are sparse. The aim was to investigate the importance of family history of VTE and CCI for short-term mortality after a first episode of VTE. Using Swedish medical databases, we conducted a 90-day nationwide cohort study of 41,700 Swedish born patients with a first-time VTE (July 2005–August 2012). Patients diagnosed with VTE and prescribed anticoagulant treatment were included. Mortality hazard ratios (HRs) with 95% confidence intervals (CIs) were determined with Cox regression. Patients with first-degree (sibling/parent) family history of VTE (n = 11,405, 27.4%) had significantly lower CCI than those without family history. Independent risk factors for 90-day mortality in the adjusted model were: female sex (HR = 1.19, 95% CI: 1.09–1.29), increasing age (HR = 1.02, 95% CI: 1.01–1.02 per year), pulmonary embolism (HR = 1.21, 95% CI: 1.11–1.32) or combined pulmonary embolism and deep venous thrombosis (HR = 1.60, 95% CI: 1.27–2.01) compared with deep venous thrombosis, CCI = 1 (HR = 2.93, 95% CI: 2.32–3.72), CCI = 2 (HR = 8.65, 95% CI: 7.16–10.46) or CCI = 3 (HR = 22.25, 95% CI: 18.73–26.44) compared with CCI = 0. Having one or two or more affected first-degree relatives with VTE was associated with lower mortality, HR = 0.83 (95% CI: 0.74–0.92) and HR = 0.65 (95% CI: 0.51–0.85), respectively. The mortality rate was 0.70% in patients with a CCI of zero. In receiver operating characteristic (ROC) analysis, the area under the ROC curve for CCI was 0.84 (0.83–0.95). Family history of VTE is associated with lower mortality while CCI is a strong predictor for short-term mortality in VTE. Co-morbidities are important for risk assessment of VTE.
Keywords: venous thromboembolism; pulmonary embolism; venous thrombosis; mortality; epidemiology